2013
DOI: 10.1038/leu.2013.145
|View full text |Cite
|
Sign up to set email alerts
|

SETBP1 mutation analysis in 944 patients with MDS and AML

Abstract: Results of a HOVON/SAKK donor versus no-donor analysis of myeloablative HLAidentical sibling stem cell transplantation in first remission acute myeloid leukemia in young and middle-aged adults: benefits for whom?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
41
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 16 publications
5
41
0
Order By: Relevance
“…9 We excluded mutations from further validation with allelic burden below 15% as these mutations cannot be validated by Sanger sequencing and their pathogenic role is unclear. SETBP1 mutations are recurrent in MDS at a low frequency, 10 and are associated with atypical chronic myeloid leukemia (CML) and ASXL1 mutations as in our patient.…”
supporting
confidence: 51%
“…9 We excluded mutations from further validation with allelic burden below 15% as these mutations cannot be validated by Sanger sequencing and their pathogenic role is unclear. SETBP1 mutations are recurrent in MDS at a low frequency, 10 and are associated with atypical chronic myeloid leukemia (CML) and ASXL1 mutations as in our patient.…”
supporting
confidence: 51%
“…Further analysis revealed SETBP1 mutations in unclassified of MDS/MPN (10%), CMML (4%), and one of four cases of CNL, but not in a wide range of other hematologic malignancies or cell lines of lymphoma and solid tumors [66]. Other investigators sought to reproduce these findings and reported SETBP1 mutation frequencies of up to 32, 7, 3, 2, and 2.5% in aCML, CMML, PMF, MDS, and secondary AML, respectively [67][68][69][70]. An association with high leukocyte counts and an independent detrimental effect on prognosis was confirmed in most but not all series.…”
Section: Setbp1 Mutations In Cnlmentioning
confidence: 99%
“…These data suggest that loss of target control by miR-142 may be a novel mechanism in the pathogenesis of leukemia. Guido Kobbe, 3 Gesine Bug, 4 Oliver Ottmann, 4 Wolf-Karsten Hofmann, 5 Nicolaus Kröger, 6 Walter Fiedler, 7 Richard Schlenk, 8 Konstanze Döhner, 8 Hartmut Döhner, 8 Jürgen Krauter, 1,9 …”
Section: 5%; P=0057)mentioning
confidence: 99%